Inovasi Manajemen Sekolah Dalam Peningkatan Mutu Pendidikan Di MAN Bengkulu Selatan - Pirmannaidi; Connie (Manajer Pendididikan, 2024)
The aim of this research is to determine the school management innovation in improving the quality of education in Madrasah Aliyah Negeri (MAN) South Bengkulu. This research used qualitative method. Data collecting technique through the observation, documentation, and interview which were tested by triangulation. The result of this research showed that the school management innovation in improving the quality of education in MAN of South Bengkulu was the students dormitory building.